Digital camera system for recording the cardinal eye position - Makino, Shinji; Hozawa, Kozue; Kanagami, Chika; Sakai, Rieko; Kondo, Reiko; Kawasaki, Tomoko; Yamamoto, Hiroko; Kurosawa, Hiromi; Sakaniwa, Atsuko; Kanagami, Sadao (JAPANESE ORTHOPTIC JOURNAL, 2002)
We tried to make shots of cardinal eye positions using a digital camera and imaging system connecting with a fundus camera. There are some advantages compared with using a regular 35mm camera. 1. Be able to make a shot faster than usual. 2. Be able to see the result on a monitor because of unnecessity to process films. 3. Be able to edit on a monitor. 4. Small space and stability of images comparing with regular method. 5. Easy to search and storage of images using database. It is very useful to make a record of cardinal eye positions using digital camera.